THE IMPACT OF ENGLISH LANGUAGE PROFICIENCY ON CODING SKILLS AND ACADEMIC PERFORMANCE IN COMPUTER ENGINEERING STUDENTS - Lika Silvia Batubara (FAKULTAS TARBIYAH INSTITUT AGAMA ISLAM SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2025)
The global nature of technology and information exchange has made English proficiency an essential skill for students in technical fields, including Computer Engineering. This study investigates the correlation between English language proficiency and academic performance, particularly coding skills, among Computer Engineering students. The research aims to determine whether a higher command of English contributes to better understanding and application of coding concepts, leading to improved academic outcomes. Utilizing a mixed-methods approach, this study collects data from both language proficiency assessments and academic performance records, with qualitative insights gathered from student interviews and coding task observations. The findings highlight that English proficiency, especially in technical vocabulary and comprehension, has a positive influence on coding abilities and overall academic success. This research underscores the importance of integrating English language development within technical curricula to enhance students' competency in globalized technical environments.